Strategi Pencegahan Kenakalan Remaja Melalui Peran Keluarga - Frendi Ismail Gulo; Selmanto Gulo; Hendrikus Otniel Nasozaro Harefa (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The rapid growth of science and technology in the contemporary era has had a considerable impact on social life, especially among adolescents. Adolescents typically encounter difficulty in controlling their emotions and desires, which can lead to deviant behavior or juvenile delinquency. This study intends to evaluate techniques for reducing juvenile delinquency through the function of the family as the first and foremost social unit in an individual's life. Using a descriptive qualitative approach, this study explores numerous literature and related previous study results. The results of the study reveal that open communication, giving affection, establishing moral and religious beliefs, and regular supervision from parents have an essential role in preventing aberrant conduct in teenagers. In addition, significant family involvement in adolescent life might enhance adolescent resilience to harmful environmental impacts. From these findings, it is recommended that families improve the quality of interactions with adolescents and work together with educational institutions and the community in establishing an environment that fosters positive adolescent development.